2018
DOI: 10.2147/copd.s172679
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of undiagnosed COPD in male patients with coronary artery disease: a cross-sectional study in Jordan

Abstract: PurposeCOPD and coronary artery disease (CAD) are common chronic diseases with shared risk factors. COPD continues to be largely underdiagnosed and undertreated. We aimed to describe the prevalence and predictors of undiagnosed COPD in Jordanian men with CAD.Patients and methodsIn a cross-sectional study conducted at a referral center in Jordan, male patients who underwent coronary angiography for suspected CAD and reported $10 pack-year of cigarette smoking were recruited. Pre- and post-bronchodilator spirome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Another study showed that, the prevalence of CHD among adults aged 45 years and older who had COPD was 12.7% [ 6 ]. Although it varies in some studies, the reported prevalence of CHD in subjects with COPD can be up to 60% [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that, the prevalence of CHD among adults aged 45 years and older who had COPD was 12.7% [ 6 ]. Although it varies in some studies, the reported prevalence of CHD in subjects with COPD can be up to 60% [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The COPD prevalence observed in our cohort (34%) is similar to that reported in prospective studies performed on IHD patients after spirometric evaluation, both in stable conditions and after PCI. 14–17 , 45 This prevalence drops to around 10% in retrospective cohorts without lung function data, suggesting that in these studies, two-thirds of COPD patients were non-diagnosed and consequently analyzed as non-COPD. 12 , 13 To our knowledge, only one prospective study performed on patients treated by PCI and with spirometric evaluation has demonstrated that COPD patients—with or without a previously known diagnosis—have a higher number of new coronary events and increased mortality after median follow-up of 3 and 6 years.…”
Section: Discussionmentioning
confidence: 70%
“…These are all indicators of the main factors that may affect the perception of QoL for these patients in Jordan, probably internationally as well. 5,11,14,15,18,33,39 Therefore, these constitute reasonable goals for the healthcare service providers and planners to target to improve the QoL perceptions among patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…It also exacerbates during physical exercise and exertion. [3][4][5][6] It is usually caused by prolonged exposure to dangerous chemicals and particles and by individual variables such as early experiences that affect lung development and heredity. Tobacco smoke exposure, indoor air pollution, occupational dust, gases, and chemicals all contribute significantly to the chance of developing COPD.…”
Section: Introductionmentioning
confidence: 99%